2018
DOI: 10.3324/haematol.2018.189365
|View full text |Cite
|
Sign up to set email alerts
|

A subset of anti-HLA antibodies induces FcγRIIa-dependent platelet activation

Abstract: HLA antibodies are associated with refractoriness to platelet transfusion, leading to rapid platelet clearance, sometimes coinciding with clinical side effects such as fever and chills. The presence of HLA antibodies is not always manifested by clinical symptoms. It is currently unclear why refractoriness to platelet transfusion is only observed in a subset of patients. Here, we utilized the availability of a unique panel of human monoclonal antibodies to study whether these were capable of activating platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…IVIg can inhibit FcγRIIa-dependent platelet activation by anti-HLA antibodies. 8 Similar effects have been observed in the context of heparin-induced thrombocytopenia. 28,29 Here, we also tested if IVIg affects complement activation and observed a dose-dependent inhibition of C3b deposition by IVIg (Figure 6A–B).…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…IVIg can inhibit FcγRIIa-dependent platelet activation by anti-HLA antibodies. 8 Similar effects have been observed in the context of heparin-induced thrombocytopenia. 28,29 Here, we also tested if IVIg affects complement activation and observed a dose-dependent inhibition of C3b deposition by IVIg (Figure 6A–B).…”
Section: Resultssupporting
confidence: 58%
“…We have recently shown that a subset of anti-HLA mAbs (including WIM8E5) can activate platelets directly through FcγRIIa in the absence of a complement source. 8 Under these conditions, WIM8E5-induced CD62P exposure was completely blocked with either anti FcγRIIa-blocking antibody IV.3 or through Syk inhibitor IV (which blocks downstream signaling of FcγRIIa 25 ) (Figure 4A). Incubation of platelets with WIM8E5 in the presence of serum as a complement source resulted in a marked increase in CD62P exposure on platelets (Figure 4A).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations